2010
DOI: 10.1103/physrevlett.104.042302
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Dynamical Origin ofP11Nucleon Resonances

Abstract: We show that two almost degenerate poles near the piDelta threshold and the next higher mass pole in the P11 partial wave of piN scattering evolve from a single bare state through its coupling with piN, etaN, and pipiN reaction channels. This finding provides new information on understanding the dynamical origins of the Roper N{*}(1440) and N{*}(1710) resonances listed by Particle Data Group. Our results for the resonance poles in other piN partial waves are also presented.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
180
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(192 citation statements)
references
References 24 publications
12
180
0
Order By: Relevance
“…Indeed, such effects are predicted e.g. in the analysis of the EBAC group [73], whereas in the Jülich framework no such bare state is needed [422]. The result is interesting because it shows that a mutually consistent description of quark-core states for the nucleon and its first radial excitation is in principle possible in such models.…”
Section: Octet and Decuplet Baryonsmentioning
confidence: 73%
See 2 more Smart Citations
“…Indeed, such effects are predicted e.g. in the analysis of the EBAC group [73], whereas in the Jülich framework no such bare state is needed [422]. The result is interesting because it shows that a mutually consistent description of quark-core states for the nucleon and its first radial excitation is in principle possible in such models.…”
Section: Octet and Decuplet Baryonsmentioning
confidence: 73%
“…Ref. [12], and the movement and conjunction of poles if rescattering effects are switched off [73]. An open issue in coupled-channel approaches is how many 'bare' states one has to include.…”
Section: Helicity Amplitudes Vs Transition Form Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those studies, the ones with dynamical-model approaches have further revealed the crucial role of (multichannel) reaction dynamics in understanding the mass spectrum, structure, and dynamical origin of baryon resonances (see, e.g., Refs. [11,12]). Similar studies based on a dynamical-model approach have also performed recently by us for the Λ * and Σ * sector [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…One is the dynamical origin of P 11 N * resonances [11]. Figure 3 shows pole positions of P 11 N * resonances extracted from a dynamical model developed in Ref.…”
Section: Multichannel Unitarity and Dynamical Coupled-channels Approamentioning
confidence: 99%